Usage of recycled fine aggregates obtained from concretes with low w/c ratio in the production of masonry plaster and mortar - Kaplan, Gokhan; Turkoglu, Mesut; Bodur, Burak; Bayraktar, Oguzhan Yavuz (Springer Science and Business Media LLC, 2021)
In this study, fresh and hardened aspects of mortars being produced from RFAs (recycled fine aggregates) obtained from concretes, w/c (water/cement) ratio of which varies in the range of 0.47–0.55 have been examined. On the mortars experiments such as those relating with workability, mechanical properties, drying shrinkage, sorptivity, and apparent porosity have been conducted. As flow diameters of mortars are kept at the value of 16 ± 2 cm, as a/c (aggregate/cement) ratio increased, w/c ratios of mortars also increased. As paste volume of mortars decreased, their mechanical properties got diminished. Increase in a/c ratio has impacted flexural strength negatively. In a mortar with a/c ratio of 5 and RFA ratio of %75, compressive strength of nearly 12 MPa has been obtained. As a/c ratio and compressive and flexural strengths of mortars increased, drying shrinkage values got reduced. Drying shrinkage value of mortars having a/c ratio of 7 and RFA ratio of %100 on 56th day has fallen below 1000 µm. By means of high grains below 75 µm within body of RFA, water penetration depth values of mortars have reduced. However, in mortars being produced by using RFA, attention should be paid to a/c ratio with regard to capillarity. Due to older cement paste situated on RFA surface, as RFA content increases, apparent porosity values of mortars have increased. As a conclusion, it has been determined that RFA will be used in production of mortar and plaster and it will be recycled and hence, sustainable building material could be obtained.
Keywords: 12. Responsible consumption